Xanthone and Flavone Derivatives as Dual Agents with Acetylcholinesterase Inhibition and Antioxidant Activity as Potential Anti-Alzheimer Agents - Inês Cruz; Ploenthip Puthongking; Sara Cravo; Andreia Palmeira; Honorina Cidade; Madalena Pinto; Emília Sousa (Journal of Chemistry)
Alzheimer’s disease (AD) is a multifactorial neurodegenerative disorder that is associated with the elderly. The current therapy that is used to treat AD is based mainly on the administration of acetylcholinesterase (AChE) inhibitors. Due to their low efficacy there is a considerable need for other therapeutic strategies. Considering that the malfunctions of different, but interconnected, biochemical complex pathways play an important role in the pathogenesis of this disease, a promising therapy may consist in administration of drugs that act on more than a target on biochemical scenery of AD. In this work, the synthesis and evaluation of xanthone and flavone derivatives as antioxidants with AChE inhibitory activity were accomplished. Among the obtained compounds, Mannich bases 3 and 14 showed capacity to inhibit AChE and antioxidant property, exerting dual activity. Moreover, for the most promising AChE inhibitors, docking studies on the target have been performed aiming to predict the binding mechanism. The results presented here may help to identify new xanthone and flavone derivatives as dual anti-Alzheimer agents with AChE inhibitory and antioxidant activities.